What can be expected from productive inclusion programs? - Jamele Rigolini (IZA World of Labor, 2016)
Productive inclusion programs provide an integrated package of services, such as grants and training, to promote self-employment and wage employment among the poor. They show promising long-term impacts, and are often proposed as a way to graduate the poor out of social assistance. Nevertheless, neither productive inclusion nor social assistance will be able to solve the broader poverty challenge independently. Rather, the future is in integrating productive inclusion into the existing social assistance system, though this poses several design, coordination, and implementation challenges.
Keywords: L26; H81; P46; P36; 330; productive inclusion; graduation; training; self-employment; entrepreneurship; social protection systems